Kinematic performance declines as group size increases during escape responses in a schooling coral reef fish - Bacchus, Monica D.; Domenici, Paolo; Killen, Shaun S.; McCormick, Mark I.; Nadler, Lauren E. (Frontiers in Fish Science, 2024)
Introduction Escaping predation is essential for species survival, but prey must effectively match their response to the perceived threat imposed by a predator. For social animals, one mechanism to reduce risk of predation is living in larger group sizes, which dilutes each individual's risk of capture. When a predator attacks, individuals from a range of taxa (e.g., fishes, sharks, and amphibians) perform an escape response, to evade the attack. Methods Using the schooling coral reef damselfish Chromis viridis, we assess if there is an optimal group size that maximizes both individual escape response performance as well as group cohesion and coordination following a simulated predator attack, comparing schools composed of four, eight, and sixteen fish. The escape response was assessed through simulated predator attacks, measuring escape latency, kinematics (average turning rate, and distance covered), and group dynamics (school cohesion and coordination). The experiments were conducted with varying group sizes to analyze the impact on escape performance and group behavior. Results We found that fish in various group sizes exhibited no difference in their reaction timing to a simulated predator attack (i.e., escape latency), but larger groups exhibited slower kinematics (i.e., lower average turning rate and shorter distance covered during the escape response), potentially because larger groups perceived the predator attack as less risky due to safety in numbers. Both school cohesion and coordination (as measured through alignment and nearest neighbor distance, respectively) declined in the 100 ms after the predator's attack. While there was no impact of group size on alignment, larger group sizes exhibited closer nearest neighbor distances at all times. Discussion The findings suggest that larger group sizes in schooling coral reef fish may lead to energy conservation by displaying less costly behavioral responses to predator threats. This potential energy saving could be attributed to a higher threshold of perceived threat required to trigger a rapid escape response in larger groups. The study emphasizes the intricate interplay between individual and collective behaviors in response to predation and sheds light on the nuanced dynamics of group living in the face of predation.